The makeshift city: towards a global geography of squatting - Vasudevan, Alexander (SAGE, 2015)
This paper introduces a set of analytical frames that explore the possibilities of conceiving, researching and writing a global geography of squatting. The paper argues that it is possible to detect, in the most tenuous of urban settings, ways of thinking about and living urban life that have the potential to reanimate the city as a key site of geographical inquiry. The paper develops a modest theory of ‘urban combats’ to account for the complexity and provisionality of squatting as an informal set of practices, as a makeshift approach to housing and as a precarious form of inhabiting the city.